Going along with the crowd? The importance of group effects for environmental deliberative monetary valuation (2017)
Deliberation is expected to enhance the validity and/or the democratic status of stated preference methods. Those objectives are challenged by the potential presence of group effects. Deference to the information publicly announced by others and social pressures to conformity prevent individuals to express their autonomous preferences. Through a split sample contingent valuation survey we tested whether participating in group discussion affects willingness to pay (WTP). We also test for the presence of group effects.  Participants in group discussion stated a higher WTP and we did not find evidence of group effects. These results are favorable to the deliberative project.